Ecotourism and Community Participation - Maxwell-Borjor Achuk Eba; Cklaimz Dorn Enamhe (dialektika kontemporer, 2023)
The term ecotourism generally refers to environmentally responsible or sustainable tourism. The extent of care and attention a homeowner puts into their house should be applied to ecotourism. Low-impact visitor behaviour, understanding and gratitude for local cultures and biodiversity, support for ecotourism conservation efforts, sustainable benefits to local communities, visitor participation in decision-making, and educational components for both the visitor and the ecotourism visitor are all characteristics of ecotourism. Ecotourism can also supplement maintenance and protection costs for protected areas and other natural areas. Ecotourism can also provide a sustainable economic development alternative for local communities with limited livelihood options. For rural people, ecotourism generates new sources of income and livelihood. This allows impoverished rural residents to expand their livelihoods and creates economic incentives to preserve natural resources. However, the extent to which these people benefit from ecotourism is contingent upon their participation in and control over the tourism industry. Ecotourism and community participation are the study's essence. This paper contends that community integration necessitates skill development and capacity building through the training of village adolescents in tourism business skills. These adolescents can establish a village-level institution to operate the ecotourism enterprise for rural community capacity building, infrastructure development, and profit sharing. Additionally, this institution would contribute to the conservation of natural resources and biodiversity. At the conclusion of the study, a structure for operationalizing community-based ecotourism management was proposed.